Bismuth Sulfide Nanorods with Retractable Zinc Protoporphyrin Molecules for Suppressing Innate Antioxidant Defense System and Strengthening Phototherapeutic Effects. Issue 10 (11th January 2019) - Cheng, Yan; Chang, Yun; Feng, Yanlin; Jian, Hui; Wu, Xiaqing; Zheng, Runxiao; Xu, Keqiang; Zhang, Haiyuan
Abstract: Bismuth (Bi)‐based nanomaterials (NMs) are widely used for computed tomography (CT) imaging guided photothermal therapy, however, the photodynamic property is hardly exhibited by these NMs due to the fast electron–hole recombination within their narrow bandgap. Herein, a sophisticated nanosystem is designed to endow bismuth sulfide (Bi2 S3 ) nanorods (NRs) with potent photodynamic property. Zinc protoporphyrin IX (ZP) is linked to Bi2 S3 NRs through a thermoresponsive polymer to form BPZP nanosystems. The stretching ZP could prebind to the active site of heme oxygenase‐1 overexpressed in cancer cells, suppressing the cellular antioxidant defense capability. Upon NIR laser irradiation, the heat released from Bi2 S3 NRs could retract the polymer and drive ZP to the proximity of Bi2 S3 NRs, facilitating an efficient electron–hole separation in ZP and Bi2 S3 NRs, and leading to reactive oxygen species generation. In vitro and in vivo studies demonstrate the promising photodynamic property of BPZP, together with their photothermal and CT imaging performance. Abstract : Zinc protoporphyrin IX (ZP) is linked to Bi2 S3 NRs with a thermoresponsive polymer to form a sophisticated nanosystem for computed‐tomography‐imaging‐guided photothermal and photodynamic therapy of cancer, in which the phototherapy efficacy is enhanced due to not only the staggered energy band levels between ZP and Bi2 S3, but also the heme oxygenase‐1 inhibiting ability of ZP.